Comparison of different techniques to study the nanostructure and the microstructure of cementitious materials with and without superabsorbent polymers. (30th October 2019) - Snoeck, D.; Pel, L.; De Belie, N.
Graphical abstract: Highlights: MIP, DVS, NMR and cryoporometry show the same trend in microstructure. The main nanometer pores have a size of 1.5–2 nm and 8–12 nm. There is a slight increase in the larger meso pore range when using SAPs. Abstract: It is difficult to study the microstructural porosity in time without destroying the samples and stopping hydration. Current techniques mainly involve mercury intrusion porosimetry and microscopic analysis. These destructive techniques are able to give information on the microstructure, but the nanostructure is affected due to sample preparation. Dynamic vapour sorption is a technique which is not often used to study the nanostructure of cementitious materials and requires the application of different models. Furthermore, nuclear magnetic resonance can be applied to non-destructive study not only the total water content but also the pore size distribution by comparing the T2 relaxation times, and can be combined with cryoporometry. In this paper, these different measuring techniques are compared and linked to each other. The obtained nano- and microstructures are compared to different models found in literature. Pore sizes in the range of 1.5–2 nm and of 8–12 nm are found, reflecting the gel pores. In addition, some bigger capillary pores are found. The measuring techniques are complementary to each other as they study different pore size ranges and are based on different phenomena.